Characterization of the microRNA408-LACCASE5 module as a regulatory axis for photosynthetic efficiency in Medicago ruthenica: implications for forage yield enhancement - Zhang, Yutong; Yan, Wei; Qiao, Yu; Gao, Xia; Tang, Fang; Gao, Cuiping; Shi, Fengling (Frontiers in Genetics, 2023)
Medicago ruthenica is closely related to Medicago sativa, a commonly cultivated forage. Characterized by its high tolerance to environmental stress, M. ruthenica is a valuable genetic resource. However, low yield limits its large-scale utilization. Leaf morphology, an important agronomic trait, is closely related to forage yield and photosynthetic efficiency. In the presented study, "Correlation of Leaf Morphology and Photosynthetic Performance with Forage Yield in Medicago ruthenica: The Underlying Molecular Mechanisms," comprehensive data analysis revealed a significant positive association between leaf width and leaf area with forage yield in Medicago ruthenica (P<0.05). The specific cultivar "Mengnong No.1 (MN No.1) had a large leaf area, and its physiological parameters related to photosynthetic characteristics were superior. Anatomical examination revealed that the leaves of MN No.1 had strong palisade tissue and compact cell structure. Subsequent investigations, utilizing small RNA and transcriptome sequencing, discerned critical miRNA-target gene networks that underpin the high photosynthetic efficiency in M. ruthenica. A total of 63 differentially expressed miRNAs (DEMs) were identified, inclusive of several well-characterized miRNAs such as miR408, miR171, and miR398. These miRNAs were predicted to target 55 genes (mRNAs), of which 6 miRNA-target gene pairs, particularly those involving miR408and miR171, exhibited inverse expression patterns. Among the six postulated miRNA-target gene pairs, the targeted cleavage of LACCASE5 (LAC5) by miR408 was conclusively validated through degradome sequencing, with the cleavage site pinpointed between the 9th and 10th nucleotides from the 5' end of miR408 via the 5'-RLM-RACE assay. Therefore, it is posited that the miR408-MrLAC5 module constitutes a central mechanism in fostering high photosynthetic efficiency in M. ruthenica. Moreover, these findings also provide valuable information for further study of the regulatory genes and miRNA functions of forage yield in legume forage.